The Textural Effect of Cu Doping and the Electronic Effect of Ti, Zr and Ge Dopings Upon the Physical Properties of In2O3 and Sn-Doped In2O3 Ceramics - S. J. Wen; G. Campet (Active and Passive Electronic Components)
The electronic properties of Cu-, Ti-, Zr-, and Ge-doped In2O3 (IO) and ITO (Sn-doped In2O3) ceramics are investigated. We distinguish the different effect of Cu doping (so called the “textural effect”) and of Ti, Zr and Ge dopings (so called the “electronic effect”) of IO and ITO ceramics. Indeed, Cu doping in IO and ITO enhances the ceramic density and thereby the conductivity due to an increase in the carrier mobility (grain boundary effect); the absorbance in the visible region is then lowered. Most interestingly for Ti-, Zr-, and Ge-doped samples, the increase of conductivity associated with an enlargement of the electron-mobility along with a decrease of the absorbance in the visible, account for the weak interactions occuring between the conduction-band electrons and the ionized donor centers.